Novel SPME fibers based on a plastic support for determination of plasma protein binding of thiosemicarbazone metal chelators: a case example of DpC, an anti-cancer drug that entered clinical trials - Reimerová, Petra; Stariat, Ján; Bavlovič Piskáčková, Hana; Jansová, Hana; Roh, Jaroslav; Kalinowski, Danuta S; Macháček, Miloslav; Šimůnek, Tomáš; Richardson, Des R; Štěrbová-Kovaříková, Petra (Analytical and bioanalytical chemistry, 2019)
Solid-phase microextraction (SPME) is an alternative method to dialysis and ultrafiltration for the determination of plasma protein binding (PPB) of drugs. It is particularly advantageous for complicated analytes where standard methods are not applicable. Di-2-pyridylketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC) is a lead compound of novel thiosemicarbazone anti-cancer drugs, which entered clinical trials in 2016. However, this agent exhibited non-specific binding on filtration membranes and had intrinsic chelation activity, which precluded standard PPB methods. In this study, using a simple and fast procedure, we prepared novel SPME fibers for extraction of DpC based on a metal-free, silicon string support, covered with C18 sorbent. Reproducibility of the preparation process was demonstrated by the percent relative standard deviation (RSD) of ≤ 9.2% of the amount of DpC extracted from PBS by several independently prepared fibers. The SPME procedure was optimized by evaluating extraction and desorption time profiles. Suitability of the optimized protocol was verified by examining reproducibility, linearity, and recovery of DpC extracted from PBS or plasma. All samples extracted by SPME were analyzed using an optimized and validated UHPLC-MS/MS method. The developed procedure was applied to the in vitro determination of PPB of DpC at two clinically relevant concentrations (500 and 1000 ng/mL). These studies showed that DpC is highly bound to plasma proteins (PPB ≥ 88%) and this did not differ significantly between both concentrations tested. This investigation provides novel data in the applicability of SPME for the determination of PPB of chelators, as well as useful information for the clinical development of DpC. Graphical abstract.
Keywords: thiosemikarbazony; Di-2-pyridylketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone; Solid Phase Microextraction; adsorpce; Rats; design vybavení; Protein Binding; krevní proteiny; Blood Proteins; křemík; Pyridines; pyridiny; Chromatography, High Pressure Liquid; skot; Antineoplastic Agents; Equipment Design; vysokoúčinná kapalinová chromatografie; Solid-phase microextraction; krysa rodu Rattus; mikroextrakce na pevné fázi; protinádorové látky; zvířata; Tandem Mass Spectrometry; Anti-cancer agents; vazba proteinů; Cattle; Sample preparation; tandemová hmotnostní spektrometrie; Thiosemicarbazones; Adsorption; Silicon; Animals